New advancement perspectives of chloride additives on enhanced heavy metals removal and phosphorus fixation during thermal processing of sewage sludge. (1st July 2018) - Saleh Bairq, Zain Ali; Li, Rundong; Li, Yanlong; Gao, Hongxia; Sema, Teerawat; Teng, Wenchao; Kumar, Sunel; Liang, Zhiwu
Abstract: Controlling the removal of heavy metals such as Copper (Cu), Zinc (Zn), lead (Pb) and cadmium (Cd) during the sewage sludge incineration and the recovery of phosphorus (P) from sewage sludge ash (SSA) remain challenging. Herein we aim to investigate the effect of the temperature, retention time and chlorinating agent additives (MgCl2 and KCl) on both the behavior of selected heavy metals and the ﬁxed rate of phosphorus (P) during sewage sludge incineration. Dry sewage sludge was mixed with various amounts of chlorinating agent and treated by a laboratory scale furnace in the temperature range of 800–1000 °C for different retention times (30, 60 and 120 min). The results demonstrated that the removal efficiency of heavy metals exhibited an increasing tendency with the addition of chloride, especially in the cases of Cu, Zn and Pb. Moreover, the temperature and retention time demonstrated significant effects on the promotion of heavy metals removal. In the case of Pb 96% was removed at 800 °C within 120 min, while 86.6% of Cd was effectively removed at 1000 °C within 30 min. MgCl2 proved to be more effective than KCl in improving the removal efficiency of heavy metals, such that up to 81.6% of Cu, 84.9% of Pb and 73.5% of Zn was removed with the addition of 15%wt Cl − /sewage sludge (SS(, At 960 °C, the boiling point of cadmium chloride CdCl2 and CdO.Al2 O3 .2SiO2 retention time and chlorinating agent had no impact on Cd removal. It was also observed that high temperature was beneficial for the transformation of non-apatite inorganic phosphorus (NAIP) to apatite phosphorus (AP). At 900 °C this transformation is efficient for Phosphate fixation, which is evidence that apatite phosphorus (AP) has the ability to be more stable than non-apatite inorganic phosphorus (NAIP) at high temperature. Highlights: The behavior of phosphorus and heavy metals during thermal processing was studied. 81.6% of Cu and 96% of Pb can be removed from sewage sludge ash. The removal efficiency of heavy metals and the Phosphate ﬁxation were studied. Sewage sludge was calcined with an inorganic chlorinating agent MgCl2 and KCl. High temperatures promote the transformation of P from NAIP to AP.